Osmanlı Dönemi Bosna – Hersek Halkının Konuştuğu Türkçe Ne Çeşit Bir Dildi? - Čaušević, Ekrem (2010)
It is known that educated Muslims in Ottoman Bosnia knew Arabic and Turkish, some of them even Persian, and they wrote literary, philosophical, philological and theological works in these languages. As far as uneducated people are concerned, it is still unclear what percentage of the population knew the Ottoman Turkish language (i.e. the spoken idiom which Nemeth dubbed Bosnian Turkish or Bosnisch-Türkisch), where and how they learned it and what the peculiarities of the idiom on all linguistic levels were. Philological research conducted on the basis of Latin script texts discovered so far points to the conclusion that this, today extinct, idiom, which non-Turkophone and ethnically heterogeneous Ottoman subjects (mostly south Slavs) used in communication with ethnic Turks, in trade and communication with representatives of local administration, differs from Turkish varieties from western Balkans, which are genetically and typologically subsumed under the west Rumelian dialect of Turkish. We hold that the west Rumelian dialect, which is the mother tongue of Turks in Bulgaria, Macedonia and Kosovo, should not be considered identical with the Turkish idiom once used by non-Turkish subjects of south Slav origin. This idiom significantly differs on all levels, and in syntax especially, from the west Rumelian dialect, and can be considered as a mixed language type (in German: Mischsprache). The Ottoman language also belongs to the mixed type, but from the sociolinguistic point of view, they are incomparable. The proposed hypothesis is further confirmed by manuscript grammars by Bosnian Franciscans (19th century), where sentences are often encountered which are but copies of syntactic forms of south Slavic languages. To illustrate, we are stating several typical examples: Bileim sen bu evde chizmekarsin joghsa agha. [Sen bu evde hizmetçi misin, ağa mısın öğrenmek istiyorum. = I would like to know whether you are servant or master in this house?] ; G’elurse g’elmezse bilmem. [Gelip gelmeyeceğini bilemem. = I don’t know if he will come.] ; Kaçinci sahat kalktun? [Saat kaçta kalktın? = When did you get up?] ; Ben Memi arkadaşlarum içün yazarum niçün onlar bilmez yazma. [Arkadaşlarım okuma yazma bilmedikleri için ben Memi bunu onlar için yazıyorum. = I’m writing this to Memo on behalf of my friends for they are illiterate.] The first Turkish studies scholar who noted the unusual features of this idiom was the Prussian consul Otto Blau, who stayed in Bosnia for a considerable period of time around the middle of the 19th century. In his book entitled Bosnisch Türkische Sprachdenkmäler, Blau wonders whether the Bosnian Turkish idiom is in fact a west Rumelian dialect, or one of the speeches of that dialect, or poorly learned Turkish. He himself compares it to children’s talk. The above-cited examples show that the Bosnian idiom can indeed be compared to the language of children who have not yet gained communicative competence. This article focuses exactly on certain peculiarities of the idiom and is an excerpt from an extensive study based on Latin-script manuscripts in Turkish.
ENG